Pentingnya Penerapan Kode Etik pada Pelayanan Keperawatan - Fadhilah, Nuur; Nursalam, Nursalam; Qur’aniati, Nuzul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to show the importance of implementing a code of ethics in services and services during the COVID-19 pandemic. The method used is a systematic review that uses PRISMA guidelines. The research results showed that 16 studies were used from 8144 articles. The majority of research used is qualitative research, randomized controlled trials and cross-sectional designs, data collection is carried out by observation, interviews and interventions in several articles. Articles taken from 2018 to 2022. The study of the code of ethics has a positive meaning for students in providing good care for learning and clinical nurses in assisting the decision-making process in ethical dilemmas, preventing the occurrence of ethically poor care services. Conclusion, the importance of hygiene ethics, in conditions where the role of ethics in dealing with dilemma situations is that nurses can still act professionally. Keywords: Code of ethics, COVID-19, Nursing